Global Humanitarian Overview 2021 - United Nations Office for the Coordination of Humanitarian Affairs (United Nations, 2020)
In 2021, 235 million people will need humanitarian assistance and protection. This number has risen to 1 in 33 people worldwide - a significant increase from 1 in 45 at the launch of the Global Humanitarian Overview 2020, which was already the highest figure in decades. The UN and partner organizations aim to assist 160 million people most in need across 56 countries and will require a total of 35 billion to do so. 2020 has been a year like no other. Amid ongoing violent conflict, rising hunger and the effects of climate change, the pandemic will continue to have an impact in 2021. As the health and non-health effects of COVID-19 merge with other shocks, humanitarian programming is also adjusting to treat it in a more integrated manner. The Global Humanitarian Overview (GHO) is the world’s most comprehensive, authoritative and evidence-based assessment of humanitarian need. Through plans that prioritize those most in need, it aims to fight hunger, killer diseases, gender-based violence and displacement.